The Definitive Guide to SQLite - Allen, Grant (Apress, 2011)
These days, applications are expected to efficiently manage an ever growing range of data. Yet it's rarely practical to embed a traditional relational database such as Oracle or MySQL within an application, due to not only size constraints but also because of the additional administrative overhead these databases require. While embeddable databases are small enough to ensure little additional total increase in application size, they often have little to offer by way of capabilities and power. So what's a developer to do?